2003
DOI: 10.1034/j.1399-6576.2003.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences on serum concentrations of morphine, M6G and M3G during routine clinical drug monitoring: A prospective survey in 300 adult cancer patients

Abstract: Patient characteristics predict only minor parts of the variability of morphine, M3G and M6G serum concentrations observed during routine clinical drug-monitoring in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 19 publications
4
27
0
1
Order By: Relevance
“…Eighteen suitable datasets were obtained [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 summarises their characteristics and the number of observations each contributed to various psychometric analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen suitable datasets were obtained [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 summarises their characteristics and the number of observations each contributed to various psychometric analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This variability was demonstrated in a study of 3,045 postsurgical patients who required anywhere from 1 to 20 boluses of morphine to obtain relief from postoperative pain [1]. Similarly, Klepstad et al [2] found considerable interindividual variation in effective serum concentrations of morphine and morphine-6-glucuronide in 300 patients with cancer. Numerous studies document that age, gender, race/ethnicity, mood states, and stress can influence the individual's pain experience.…”
Section: Introductionmentioning
confidence: 95%
“…We then studied the effects of the three MOR agonists, morphine, DAMGO and fentanyl, used in a wide range of concentrations (1 nM-10 mM ), which includes concentrations similar to brain extracellular levels of endogenous opioids and clinically relevant concentrations of exogenous opioid agonists. Thus morphine, fentanyl and DAMGO were applied at concentrations (10 -9 to 10 -5 M) that included the nanomole regime covering the range of clinically relevant brain concentrations (Bouw et al, 2001), the opioid concentrations found in the cerebrospinal fluid (Bernards et al, 2003) or the plasma/serum (Veselis et al, 1994;Klepstad et al, 2003;Gunnar et al, 2004;Solassol et al, 2005) as well as the extracellular levels of endogenous brain opioids (~1 to 10 nM) (Lam et al, 2008).…”
Section: Figurementioning
confidence: 99%